Mechanistic understanding of catalysis by combining mass spectrometry and computation. Issue 85 (27th September 2019) - Cheng, Gui-Juan; Zhong, Xiu-Mei; Wu, Yun-Dong; Zhang, Xinhao
Abstract : The combination of mass spectrometry and computational chemistry has been proven to be powerful for exploring reaction mechanisms. The former provides information of reaction intermediates, while the latter gives detailed reaction energy profiles. Abstract : Mechanistic studies are of great importance for the understanding, optimization, and design of chemical reactions, especially catalysis. In recent years, the combination of mass spectrometry and computational chemistry has been proven to be powerful and effective for the exploration of reaction mechanisms. The former provides information of possible reaction intermediates, which are difficult to obtain using other experimental methods, while the latter gives detailed structural information of reaction intermediates and explores reaction energy profiles. This review covers applications of the combined method and highlights its strengths in mechanistic studies. Representative works are discussed to demonstrate the complementarity and synergy of mass spectrometry and computational chemistry. Some challenges in mechanistic studies with these tools and their possible solutions, as well as the trend for future developments are also discussed.